The Effect of Cooperative Learning Type Teams Games Tournament (TGT) on Creativity and Comprehension the Student’s Concept in Mathematics Learning - Anisa Ramadiana; Akhsanul In'am; Adi Slamet Kusumawardana (Department of Mathematics Education University of Muhammadiyah Malang, 2019)
This study aims to effect of the TGT learning model on student’s creativity and comprehension of concepts in mathematics learning. This study used quasi-experimental research. The population in this study were 256 students of class VIII SMP YPPSB. The research sample was obtained in class VIII-H of 32 students as the experimental class and class VIII-D with total of the students were 31 students as the control class. The test used to analyze the research data was the Independent Sample T-test on the posttest results. The results of the study showed that creativity and comprehension of concepts using the TGT learning model was better than the class that used conventional learning. The average creativity used the TGT learning model tcount = 4.080 and the average comprehension of the concept of tcount = 11.012 with ttable = 2.00 which means tcount> ttable. Thus, the TGT type learning model has a significant influence on student’s creativity and comprehension of concepts in mathematics learning.